Objective and subjective measures of neighborhood environment (NE): relationships with transportation physical activity among older persons - Nyunt, Ma Shwe Zin (Int J Behav Nutr Phys Act, 2015)
BACKGROUND: This study examined the associations of subjective and objective measures of the neighbourhood environment with the transportation physical activity of community-dwelling older persons in Singapore. METHOD: A modified version of the Neighborhood Environment Walkability Scale (NEWS) and Geographical Information System (GIS) measures of the built environment characteristics were related to the frequency of walking for transportation purpose in a study sample of older persons living in high-density apartment blocks within a public housing estate in Singapore. Relevant measured variables to assess the complex relationships among built environment measures and transportation physical activity were examined using structural equation modelling and multiple regression analyses. RESULTS: The subjective measures of residential density, street connectivity, land use mix diversity and aesthetic environment and the objective GIS measure of Accessibility Index have positively significant independent associations with transportation physical activity, after adjusting for demographics, socio-economic and health status. CONCLUSION: Subjective and objective measures are non-overlapping measures complementing each other in providing information on built environment characteristics. For elderly living in a high-density urban neighborhood, well connected street, diversity of land use mix, close proximity to amenities and facilities, and aesthetic environment were associated with higher frequency of walking for transportation purposes.